The Outer Limits, by Joanne Morreale - Mehdi Achouche (Alphaville: Journal of Film and Screen Media, 2024)
Netflix’s Black Mirror (2011–present) is often compared to The Twilight Zone (1959–1964) for its thoughtful science fiction (SF) commentary on contemporary society. Yet, as Joanne Morreale shows in her excellent study of The Outer Limits (1963–1965), it might be with that less well-known SF series that Black Mirror should be compared. The confusion that often occurs between episodes from The Twilight Zone and The Outer Limits highlights the many similarities between the two series, with the former’s success paving the way for the latter. Morreale’s concise book, the latest in the TV Milestones series by Wayne State University Press, can only help bring back into the spotlight a series which over the decades has been unfairly living in the shadow of The Twilight Zone.